Effect of increasing load on the MILD combustion of COG and its blend in a 30 kW furnace using low air preheating temperature. (August 2017) - Mosca, Gabriele; Lupant, Delphine; Lybaert, Paul
Abstract: MILD combustion is a high efficiency technique, applied on industrial furnaces to have low polluting emissions and significant energy saving by high air preheating. The main purpose of this work was the investigation of the behavior of two fuels rich in H2 burning in MILD regime at different furnace temperature levels (1200 K ÷ 1300 K), using air preheating temperature which can be guaranteed by low performance heat exchanger too. Both fuels had very good performance but the one with higher H2 content, which reduces the ignition delays, showed higher capability to keep a well-positioned reaction zone at higher heat transfer to the load and consequently wider flue gases temperature range.